PENGARUH KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA RUMAH MAKAN SARI INDAH H.KOMAR DI SITUBONDO - Firdiansyah, Ferry; Ediyanto, Ediyanto; Kusnadi, Edy (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The restaurant is a business in the field of catering services that provides services for ordering food and drinks and provides a place to enjoy the dishes in the restaurant. The purpose of this study was to analyze and examine the effect of product quality and word of mouth on consumer loyalty through consumer satisfaction at Sari Indah H.Komar Restaurant in Situbondo. This research is an explanatory research. The population in this study were consumers of Sari Indah H.Komar Restaurant. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product quality has a significant effect on consumer satisfaction, word of mouth has a significant effect on consumer satisfaction, product quality has a significant effect on consumer loyalty, word of mouth has a significant effect on consumer loyalty through consumer satisfaction, Consumer Satisfaction has a significant effect on Consumer Loyalty, Product Quality has an effect on Consumer Loyalty through Consumer Satisfaction, Word of Mouth has a significant effect on Consumer Loyalty through Consumer Satisfaction.